2011
DOI: 10.1016/j.biopsych.2011.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Interneuron-Specific ErbB4 Expression in Frontal Cortex of Rodents, Monkeys, and Humans: Implications for Schizophrenia

Abstract: Background Neuregulin-1 and ErbB4 are genetically associated with schizophrenia, and detailed knowledge of the cellular and subcellular localization of ErbB4 is important for understanding how neuregulin-1 regulates neuronal network activity and behavior. Expression of ErbB4 is restricted to interneurons in the rodent hippocampus and cortex. However, controversy remains about the cellular expression pattern in primate brain and its subcellular distribution in postsynaptic somatodendritic locations versus presy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 50 publications
9
86
2
Order By: Relevance
“…The important association of γ oscillations with attention, working memory, and other cognitive functions (1), and their perturbation in numerous psychiatric disorders (2,3,42,43), underscores the potential therapeutic value of targeting networks that generate and regulate γ oscillations. We propose, on the basis of the functional properties and expression of ErbB4 and D4Rs in PV+ interneurons in the dorsal lateral prefrontal cortex (21,25) and hippocampus (this study), as well as their effects on KA-induced γ oscillations and plasticity (18,19), that these receptors are well situated to modulate network activity that impacts cognition. The fact that D4R-specific antagonists were found to be ineffective as antipsychotics for the treatment of schizophrenia (44,45) does not negate the potential use of D4R targeting drugs to treat cognitive deficits, as suggested by studies in primates and rodents (39,40,46,47).…”
Section: Significance Of Erbb4 and D4 Receptor Expression In Pv+ Gabamentioning
confidence: 94%
See 1 more Smart Citation
“…The important association of γ oscillations with attention, working memory, and other cognitive functions (1), and their perturbation in numerous psychiatric disorders (2,3,42,43), underscores the potential therapeutic value of targeting networks that generate and regulate γ oscillations. We propose, on the basis of the functional properties and expression of ErbB4 and D4Rs in PV+ interneurons in the dorsal lateral prefrontal cortex (21,25) and hippocampus (this study), as well as their effects on KA-induced γ oscillations and plasticity (18,19), that these receptors are well situated to modulate network activity that impacts cognition. The fact that D4R-specific antagonists were found to be ineffective as antipsychotics for the treatment of schizophrenia (44,45) does not negate the potential use of D4R targeting drugs to treat cognitive deficits, as suggested by studies in primates and rodents (39,40,46,47).…”
Section: Significance Of Erbb4 and D4 Receptor Expression In Pv+ Gabamentioning
confidence: 94%
“…Expression of ErbB4 receptors is restricted to ∼50% of GABAergic PV+ interneurons in the rodent hippocampus (20), whereas in the frontal cortex most ErbB4-positive interneurons also express PV (21). Interestingly, in ErbB4 null mice, enhancement of KA-induced γ oscillation power by NRG-1 is absent, and there is an ∼60% reduction in endogenous γ oscillation power that coincides with a loss of PV+ interneurons (19).…”
Section: Significance Of Erbb4 and D4 Receptor Expression In Pv+ Gabamentioning
confidence: 99%
“…Four-to 6-wk-old Sprague-Dawley rats were transcardially perfused with 4% paraformaldehyde (PFA) in 0.1 M PBS (pH 7.4). Brains were postfixed overnight in the same fixative, and 50-μm free-floating sections were stained and analyzed as described (9,10). All animal protocols were approved by National Institute of Child Health and Human Development (NICHD) Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…In the neocortex and hippocampus of rodents, monkeys, and humans, ErbB4 expression is restricted to GABAergic interneurons, and its expression is particularly high in parvalbumin-positive fastspiking (PV+) interneurons (8,9). Of note, targeted ablation of ErbB4 specifically in PV+ interneurons recapitulates behavioral abnormalities of full ErbB4-null mice, highlighting the importance of ErbB4 signaling in this GABAergic interneuron subclass (10).…”
mentioning
confidence: 99%
“…ErbB4 shows conserved interneuron-specific expression in mice, rats, monkeys, and humans (Neddens et al, 2011) and NRG1/ErbB4 signaling is necessary for the development of inhibitory circuits (Del Pino et al, 2013;Fazzari et al, 2010). Neddens et al (2011) also showed that ErbB4 expression was restricted to cells that express interneuron subclass markers PV, CCK, or CR, but not those that express CB, which is particularly interesting since CB interneurons are also those that appear to be unaffected in schizophrenia (Lewis et al, 2005). NRG1/ErbB4 signaling also appears to have distinct functions in development and maintenance of cortical circuitry.…”
Section: Gene Effects Converge Onto Gaba System Developmentmentioning
confidence: 99%